FlashTag-mediated Labeling for Intraventricular Macrophages in the Embryonic Brain - Hisa Asai; Mizuki Ono; Takaki Miyata; Yuki Hattori (Bio-Protocol)
The fate mapping technique is essential for understanding how cells differentiate and organize into complex structures. Various methods are used in fate mapping, including dye injections, genetic labeling (e.g., Cre-lox recombination systems), and molecular markers to label cells and track their progeny. One such method, the FlashTag system, was originally developed to label neural progenitors. This technique involves injecting carboxyfluorescein diacetate succinimidyl ester (CFSE) into the lateral ventricles of mouse embryos, relying on the direct uptake of dye by cells. The injection of CFSE into the lateral ventricle allows for the pulse labeling of mitotic (M-phase) neural progenitors in the ventricular zone and their progeny throughout the brain. This approach enables us to trace the future locations and differentiation paths of neural progenitors. In our previous study, we adapted this method to selectively label central nervous system–associated macrophages (CAMs) in the lateral ventricle by using a lower concentration of CFSE compared to the original protocol. Microglia, the brain's immune cells, which play pivotal roles in both physiological and pathological contexts, begin colonizing the brain around embryonic day (E) 9.5 in mice, with their population expanding as development progresses. The modified FlashTag technique allowed us to trace the fate of intraventricular CAMs, revealing that certain populations of microglia are derived from these cells. The optimized approach offers deeper insights into the developmental trajectories of microglia. This protocol outlines the modified FlashTag method for labeling intraventricular CAMs, detailing the CFSE injection procedure, evaluation of CFSE dilution, and preparation of tissue for immunohistochemistry.